The prophet's heir : the life of ʻAlī ibn Abī Ṭālib - Abbas, Hassan, 1969- (Yale University Press, 2021)
The life and legacy of one of Mohammad's closest confidants and Islam's patron saint: Ali ibn Abi Talib.